2018
DOI: 10.1115/1.4041667
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Computational Fluid Dynamics Simulations and Experiments for Stratified Air-Water Flows in Pipes

Abstract: Stratified gas–liquid flow is a flow regime typically encountered in multiphase pipelines. The understanding and modeling of this regime is of engineering importance especially for the oil and gas industry. In this work, simulations have been conducted for stratified air–water flow in pipes. We solved the Reynolds-averaged Navier–Stokes (RANS) equations with the volume of fluid (VOF) method. The aim of this work was to evaluate the performance of the k–ω shear stress transport (SST) turbulence model with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The simulation results are validated against the numerical simulation by Chinello et al (2019) and experimental data reported in Espedal (1998). In particular, monophase and stratified flow behaviours induced by leaks are compared and validated with the experimental data reported by Monina-Espinosa et al (2013).…”
Section: Related Workmentioning
confidence: 90%
See 1 more Smart Citation
“…The simulation results are validated against the numerical simulation by Chinello et al (2019) and experimental data reported in Espedal (1998). In particular, monophase and stratified flow behaviours induced by leaks are compared and validated with the experimental data reported by Monina-Espinosa et al (2013).…”
Section: Related Workmentioning
confidence: 90%
“…The VOF method, which is a one-fluid approach, comprises the continuity and momentum equations which are given in Equations ( 1) and (2), respectively (Chinello et al, 2019):…”
Section: Governing Equationsmentioning
confidence: 99%
“…They have only focused on stratified flows of water-air mixtures at atmospheric conditions, and the Computational Fluid Dynamic (CFD) models have not predicted flow conditions accurately with small liquid holdups (Ghorai and Nigam, 2006;Kumar and Ming Bing, 2011;Karami et al, 2014). Even some of the most recent studies, such as Chinello et al(2019) andL opez et al (2016), simulated only liquid holdups over 10% and even then reported errors of up to 30% for flows whose holdups were near this threshold value.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that the rapid increase in pressure is related to the length of the slugs. In addition to the experimental studies, several numerical studies were carried out on two-phase flows [32]- [41].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained using the VOF model agree well with the experimental data, especially for low gas velocities. Other research [34]- [36], [41] examined the ability of numerical models to predict the development and characteristics of intermittent flows (slug flow and plug flow). Nasrfard et al [34] simulated two-phase flow in a 14.4 m long pipe with an inside diameter of 54 mm.…”
Section: Introductionmentioning
confidence: 99%